Dielectric tunability in (1-x)[Pb(Mg1/3Nb2/3)O-3]-xPbTiO(3) ceramics for tunable devices application - Guarany, C. A.; Guerra, J. D. S.; Araujo, E. B. [UNESP]; Lima, E. C. [UNESP]; IEEE (Ieee, 2010)
The dielectric properties of the 0.65[Pb(Mg1/3Nb2/3)O-3]-0.35PbTiO(3) ferroelectric ceramic composition were investigated viewing the capability to be used for tunable microwave applications. The dielectric response has been studied for three selected temperatures (300 K, 370 K and 400 K), below the paraelectric-ferroelectric phase transition temperature, as a function of the applied 'bias' electric field. The obtained dielectric tunability was found to be around 60 %, under an electric field of 19 kV/cm, which makes the studied ceramic composition an excellent candidate for application in the electro-electronic industry, as tunable devices.
Keywords: ceramics; ferroelectrics; dielectric properties